KARAKTERISTIK IBU BERHUBUNGAN DENGAN PEMILIHAN TENAGA PENOLONG PERSALINAN - Karningsih Karningsih; Mardiana Mardiana; Therssia Therssia (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Data base of Dinkes Sukabumi year 2013shows that delivery process attended by healthprofessional is 59,70% from total delivery in West Java. This research aims to identify thecorrelation between mothers characteristic andtheir choice to give birth with healthpractitioner or other care giver, in the Ginanjar village, Sukabumi. This research isquantitative approach with the use of cross-sectional design. The sample are92 motherswho gave birth between January and December 2013. The results shows that the numberof mothers give birth assisted by a shaman is 42%. This study proves the existence of arelationship between education mothers, occupation mothers, ANC examination history andthe choice ofbirth attendant with p value < 0.05. Mutivariate analysis shows that ANCexamination history is thedominant factor, which influence mothers choice with OR 5,784.Conclusion: the number of deliveries attended by shamans is high. Promoting healthpractitioners attendance in deliveries is required. There is a need to collaborate and sharerole amonghealth workers, cadres, shamans and communityto safedelivery.